(A) Symmetric impacts of crime rate on total factor productivity: evidence from Nigeria. Issue 2 (5th November 2021) - Ajide, Folorunsho M.
Abstract : Purpose: In this study, an investigation into the asymmetric impacts of crime rate on total factor productivity (TFP) in Nigeria is conducted. Design/methodology/approach: The study employs linear and non-linear autoregressive distributed lag (ARDL) modelling techniques to analyse Nigerian data spanning over a period of 1986–2017. In addition, Granger causality tests are conducted under error correction technique. Findings: The study establishes that crime rate has a significant impact on TFP in the short and long run. In addition, the positive component of crime rate has positive impacts on TFP in the short run while the negative shocks have negative impacts on TFP. However, in the long run, both positive and negative components have negative impacts on TFP in Nigeria. Originality/value: This study is the first to analyse the asymmetric impact of crime rate on TFP. The study also advances the literature by examining the symmetric impact of crime rate on TFP in an African country (Nigeria) where crime-related activities are rampant. The study is one of the few studies that shed light on nonlinearities in criminal behaviour.